PERENCANAAN JUMLAH PRODUKSI OPTIMAL UNTUK MEMBERIKAN PENDAPATAN MAKSIMAL DI PT. CCAI CENTRAL SUMATERA - Meldia Fitri; Ali Sutan Nasution (Sekolah Tinggi Teknologi Industri Padang, 2016)
PT. Coca Cola Amatil Indonesia (CCAI) is a company engaged in the manufacture of soft drinks agro-industry. In the process of production of PT. CCAI has decreased the amount of production in 2013. To overcome this problem, researchers interested in more depth about the function of the simplex method for optimal production quantities and the maximum income that can be obtained by PT. CCAI.Simplex method is a method of solving problems through recalculation linear program (iteration) which measures the same calculation is repeated many times before the optimum solution is achieved. Simplex method is used to solve the case with many decision variables. In this study, the calculation of the simplex method using software lingo10, variable objective function simplex method in this study is the selling price of the product, raw material concentrates, sugar raw materials, raw materials and raw materials CO2 syrup. From the calculations have been done obtained optimal production quantities which produces Coca Cola 295ml many as 440547.8 crates / year, as many as 44604.35 crates Sprite 295ml / 220ml Frestea year and as many as 464847.8 crates / year so thatthe maximum income to be obtained by the company amounted to USD 2.235097 billion.Keywords: production, simplex method, revenue, software lingo10